WILD TURKEY BROOD HABITAT USE AND CHARACTERISTICS IN COASTAL PLAIN PINE FORESTS - Jason C. Peoples; D. Clay Sisson; Dan W. Speake (Wildlife Society Bulletin)
Abstract: The availability and quality of brood habitat may limit wild turkey (Meleagris gallopavo silvestris) populations. We examined habitat selection and quantified habitat characteristics of brood and nonbrood areas in southern Georgia and northern Florida from 1991 to 1993 to determine factors important in successful brood rearing. Hens with broods (0‐28 days old) preferred forest openings relative to other habitats (P ≤ 0.05). Invertebrate volume was greater (P < 0.01) in brood areas than in nonbrood areas and was greater (P < 0.05) in brood areas of successful hens than in those of unsuccessful hens. Brood habitat was characterized by less basal area per hectare (P < 0.01), less overstory canopy closure (P < 0.01), higher density of vegetation from 0 to 30 cm above the ground (P ≤ 0.02), and lower density of vegetation from 60 to 120 cm above the ground (P < 0.04) than nonbrood areas. Successful brood areas were characterized by less overstory canopy closure (P < 0.01), higher density of vegetation from 10 to 30 cm above the ground (P < 0.02), and lower density of vegetation from 40 to 100 cm above the ground (P ≤ 0.05) than unsuccessful brood areas.